PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA SCRAPBOOK TERHADAP PENGETAHUAN PERENCANAAN MAKANAN DAN TINGKAT KONSUMSI IBU HAMIL ANEMIA DI WILAYAH KERJA PUSKESMAS HARAPAN BARU: PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA SCRAPBOOK TERHADAP PENGETAHUAN PERENCANAAN MAKANAN DAN TINGKAT KONSUMSI IBU HAMIL ANEMIA DI WILAYAH KERJA PUSKESMAS HARAPAN BARU - Hana Nur'faizah; Joko Cahyono; Diah Retno Wahyuningrum (HSG (Health Science Growth) Journal, 2023)
Anemia in pregnant women can occur due to a doubling of iron requirements due to increased blood volume and fetal growth. Providing nutrition education is an alternative that can provide basic knowledge needs for pregnant women and is more effective by using scrapbook media. The purpose of this study was to determine the effect of nutrition education using scrapbook media on food planning knowledge and consumption levels of anemic pregnant women in the Harapan Baru Health Center working area. Pre-experiment research with One Group Pretest-Posttest design. The sampling technique used purposive sampling consisting of 18 respondents. Data collection using questionnaires and 24-hour food recall interviews for 3 non-consecutive days. Univariate analysis technique with descriptive and bivariate analysis with Wilcoxon test. The results showed that there was an effect of nutrition education using Scrapbook media on the food planning knowledge of anemic pregnant women (p = 0.000) and there was no effect of nutrition education using Scrapbook media on the consumption levels of anemic pregnant women energy, protein, fat, carbohydrates respectively (p = 0.131; p = 0.257; p = 0.114; p = 0.59). Conclusion: There is an effect of nutrition education using scrapbook media on the food planning knowledge of anemic pregnant women and there is no effect of nutrition education using scrapbook media on the consumption level of anemic pregnant women in the Harapan Baru Health Center working area.